2018
DOI: 10.1007/s10741-018-9697-9
|View full text |Cite
|
Sign up to set email alerts
|

Expanded algorithm for managing patients with acute decompensated heart failure

Abstract: Heart failure is a complex disease process, the manifestation of various cardiac and noncardiac abnormalities. General treatment approaches for heart failure have remained the same over the past decades despite the advent of novel therapies and monitoring modalities. In the same vein, the readmission rates for heart failure patients remain high and portend a poor prognosis for morbidity and mortality. In this context, development and implementation of improved algorithms for assessing and treating HF patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 93 publications
0
11
0
1
Order By: Relevance
“…Considering the unacceptably high rates of mortality following hospitalization for ADHF and worse prognosis with recurrent hospitalizations, it is critical to find a standard approach to evaluating these patients before discharge to decrease rehospitalizations. 164 Rehospitalization is often related to inadequate decongestion during index hospitalization with poor appreciation of continued hemodynamic congestion in the absence of overt clinical congestion. The following tools can assist in appropriately evaluating patients before discharge.…”
Section: Evaluation Of Discharge Readinessmentioning
confidence: 99%
“…Considering the unacceptably high rates of mortality following hospitalization for ADHF and worse prognosis with recurrent hospitalizations, it is critical to find a standard approach to evaluating these patients before discharge to decrease rehospitalizations. 164 Rehospitalization is often related to inadequate decongestion during index hospitalization with poor appreciation of continued hemodynamic congestion in the absence of overt clinical congestion. The following tools can assist in appropriately evaluating patients before discharge.…”
Section: Evaluation Of Discharge Readinessmentioning
confidence: 99%
“…These conditions include coronary artery disease, hypertension, myocardial disease, pericardial disease, cardiac electrical abnormalities (atrial fibrillation of specific worse outcome), valvular disease, renal disease, iron deficiency, lung disease (especially COPD with patients complaining of dyspnoea), diabetes mellitus and as well as non-adherence to treatment. 13…”
Section: Identify and Treat Significant Co-morbiditiesmentioning
confidence: 99%
“…15 c. Continue the use of or begin therapies known to decrease hospital readmissions. 13 It has been shown that initiation of guideline-directed-medical-therapy of heart failure in hospital rather than post-discharge leads to higher adherence to prescribed medications, at least for 60 days of follow-up evaluations.…”
Section: Avoid Potentially Harmful Therapiesmentioning
confidence: 99%
“…Acute decompensated Heart failure (ADHF) is mostly defined as a clinical syndrome characterized by worsening signs or symptoms of heart failure (HF) requiring unscheduled hospital visits or medical care. 1 Despite its significant contribution to the increasing health burden with high in-hospital mortality (3%–8.7%), post-discharge mortality (8%–31%), and re-hospitalization (6%–38.1%), risk stratification scores are less commonly used in these patients. 1 , 2 , 3 In the presence of multiple risk prediction models for HF, precisely predicting the risk in patients with ADHF becomes difficult.…”
Section: Introductionmentioning
confidence: 99%